The unexpected occurrence of late Sardina pilchardus (Walbaum, 1792) (Osteichthyes: Clupeidae) larvae in a temperate estuary - Morais, P. (2009)
The presence of sardine larval stages inside estuaries has generally been regarded as accidental and restricted to the lower part of estuaries. Sampling done with a zooplankton net in the Guadiana estuary corroborated this hypothesis. Late sardine larvae (32.8 ± 2.0 mm) were, however, unexpectedly collected with an otter trawl, 14 km upstream from the mouth of the estuary. Thus, this work intends to: (1) discriminate and compare the abiotic characteristics of the sites where maximum abundance of sardine larval stages were registered, when captured with a zooplankton net, with the characteristics of the sites where late sardine larvae were collected with an otter trawl; (2) demonstrate that the presence of the late sardine larvae inside the Guadiana estuary was not accidental. The average salinity of the site were late larvae where collected was 4.2 ± 2.3, i.e. 87.3% lower than the average salinity where maximum abundance of early larvae was registered. We suggest that the presence of the late sardine larvae inside the Guadiana estuary was not accidental. In order to migrate to that location and remain in the estuary, counteracting river inflow, these late larvae must have employed active migration and retention strategies. New methodologies need to be implemented for routine sampling of all larval stages of sardine, in order to achieve a complete understanding of their life cycle.